2019
DOI: 10.2147/ppa.s191482
|View full text |Cite
|
Sign up to set email alerts
|

<p>Pharmacist-led medication non-adherence intervention: reducing the economic burden placed on the Australian health care system</p>

Abstract: Background: Scarcity of prospective medication non-adherence cost measurements for the Australian population with no directly measured estimates makes determining the burden medication non-adherence places on the Australian health care system difficult. This study aims to indirectly estimate the national cost of medication non-adherence in Australia comparing the cost prior to and following a community pharmacy-led intervention. Methods: Retrospective observational study. A d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 32 publications
1
23
0
4
Order By: Relevance
“…Better use of medicines can improve quality of life through reduced hospitalisations and improved health outcomes such as morbidity and mortality. 4 In a low-and-middle-income country, such as India, it is imperative to note that this financial loss is higher. 5 Various factors responsible for non-adherence have been identified-gender, ethnicity, occupation, duration of disease, stress, substance abuse, forgetfulness, lack of family support, high case load of health facilities etc.…”
Section: Introductionmentioning
confidence: 99%
“…Better use of medicines can improve quality of life through reduced hospitalisations and improved health outcomes such as morbidity and mortality. 4 In a low-and-middle-income country, such as India, it is imperative to note that this financial loss is higher. 5 Various factors responsible for non-adherence have been identified-gender, ethnicity, occupation, duration of disease, stress, substance abuse, forgetfulness, lack of family support, high case load of health facilities etc.…”
Section: Introductionmentioning
confidence: 99%
“…In many countries, medication education is one of the evaluation indicators for clinical pharmacists and has been proved to increase treatment adherence . It has been reported in Australia that the cost of non‐adherence per adult dropped by $95 as PIs saved the Australian healthcare system and patients $1.9 billion annually . Moreover, ADEs can be prevented with better guidance on adherence .…”
Section: Resultsmentioning
confidence: 99%
“…This study also found a significant increase in medication adherence in the intervention group compared with controls 27 . A study conducted in Australia also found that a pharmacist-led intervention targeted to patients with hypertension, dyslipidemia, or depression saved US$1.9 billion annually 28 . This suggests that similar programs targeted to COPD patients might also yield health economic benefits.…”
Section: Discussionmentioning
confidence: 99%